Spiritual and Community-Based Mental Health Services for Children with Special Needs in Islamic Boarding School - Moordiningsih, Moordiningsih; Kristiati, Aspi; Supartini, Ninik; Bayu Krisnadewara, Pradinta; Astari, Pritania; Agusno, Mahar; Pradhana Mahar, Hanindita Budhi (Jurnal Psikologi, 2024)
This study focuses on enhancing the care and educational support for children with special needs, particularly in rural areas where their families often lack adequate support. Recognizing the vital roles of communities and governments, the research seeks to create an inclusive education and mental health service model that incorporates spirituality and community engagement. A qualitative research method was used to achieve this, involving 19 managers and caregivers of children with special needs. Through interviews, participant observations, and three focus group discussions, data were collected using the free association technique and analyzed via thematic analysis. This analysis highlighted four key themes: the development of spiritual and community-based mental health services, the application of these approaches in service delivery, the care strategies for children with special needs, and the evaluation methods and psychological interventions rooted in indigenous psychology. The goal is to establish a mental health service model for rural settings that can be adapted for broader application in other regions.